Student incentives and diversity in college admissions - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2009)
This paper examines student incentives when faced with a college admissions policy which pursues student body diversity. The effect of a diversify-conscious admissions policy critically depends on the design of the policy. If the admissions policy fails to incentivize students from a disadvantaged socioeconomic background it may lead to a deterioration in the intergroup score gap while failing to improve student body diversity in equilibrium.
hdl:10197/2608
Keywords: H0; J7; 330; Affirmative action; College admissions; All-pay auction; Contest; Tournament